INOVASI PELAYANAN NING YAONAH (NIKMATNYA NGANTRI DAN PELAYANAN ONLINE MUDAH) UNTUK MENCIPTAKAN KEPUASAN MASYARAKAT OLEH DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN JOMBANG - Saputri Saputri; Meirinawati Meirinawati (Publika, 2022)
Publik agencies develop to provide satisfaction for the community through innovations to match the expectations of the community. One of them is innovation in technology. The implementation of public service innovations in the form of population administration in Jombang Regency is realized in a system called Ning Yonah. The inauguration of the online system took place in 2021 against the backdrop of the Covid-19 pandemic and wanting to make it easier for the public to apply for a system that can access the entire service process. However, in the process, several complaints were encountered by the community, such as obstacles to technological stuttering and procedures for using it. The purpose of the study was to explain the innovation of the service Ning yaonah to create community satisfactoin by service Ning Yaonah to create community satisfactoin by the population and civil regristry office of Jombang regency. The theory in research uses the stages of innovation according to Sherwood. Data collectoin techniques using observation, interviews, and documentation. The interview subject were employees of the Jombang regency population and civil regristry office. Data analysis consists of data collection, reduction, presentation, and drawing conclusions. The result of the research based on Sherwood, produced the ideas, Ning Yaonah is an innovation product from the pupulation and civil regristration office of Jombang regency, which was born against the backdrop of the Covid-19 pandemic and is an effort to update existing applications. Evaluating the idea, the existence of Ning Yaonah meets the needs and expectations of the community compared to services carried out directly at the Jombang regency population and civil regristry office. Implementation of the idea, the population and civil regristry office of Jombang regency carried out socialization efforts to the community in stages, both directly and through social media so that it was right on target and the public could easily use it. Keywords: Public service, Innovation, Ning Yaonah